2007
DOI: 10.1111/j.1095-8312.2007.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

The first humans travelling on ice: an energy-saving strategy?

Abstract: Economy of locomotion is a constant challenge for animals, particularly when related to migrations and travelling. The present study focuses on human locomotion and particularly on the development of ice skating. The aim of our research was to understand whether an environmental feature such as a strong presence of lakes (frozen in winter) could force humans to develop ice skates in order to limit the energy cost of travelling. We hypothesized that the energy-saving principle was a determinant factor in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Yet the few studies which have detailed camel distribution have noted that camels do not appear to avoid rocky, range habitats as previously suggested 56 . Other studies have suggested, based on fossil evidence of Paracamelus, that the dromedary camel may have descended from a larger boreal browser, whose fat pads evolved as an adaptation in cold climates to traverse over snow 37 -much like humans wearing snow shoes 57,58 . While having larger fat pads would certainly reduce the tendency for feet to sink into sand or snow 59 , the relative influences of body mass and habitat on fat pad function are difficult to unravel.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the few studies which have detailed camel distribution have noted that camels do not appear to avoid rocky, range habitats as previously suggested 56 . Other studies have suggested, based on fossil evidence of Paracamelus, that the dromedary camel may have descended from a larger boreal browser, whose fat pads evolved as an adaptation in cold climates to traverse over snow 37 -much like humans wearing snow shoes 57,58 . While having larger fat pads would certainly reduce the tendency for feet to sink into sand or snow 59 , the relative influences of body mass and habitat on fat pad function are difficult to unravel.…”
Section: Discussionmentioning
confidence: 99%
“…Outdoor ice skating may have first been used as a form of transportation thousands of years ago with the aid of bone skates (Formenti and Minetti ). In modern times, ice skating provides important recreational benefits such as activity, social capital, and cohesion, as well as a sense of place and connection to one's heritage (Visser and Petersen ; Liu et al ).…”
Section: Warm Winters and Losses In Ice‐derived Cultural Ecosystem Sementioning
confidence: 99%
“…The energy-saving principle was hypothesised to be a determinant factor in the birth of bone skates (Formenti and Minetti 2008). These authors created replicas of ancient bone skates, and measured velocity and metabolic energy cost of bone skating.…”
Section: Skating On Animal Bones May Have Reduced Time and Energy Cosmentioning
confidence: 99%